Secure MDM-OFDM-Ro-FSO system using HG modes - Amphawan, Angela; Chaudhary, Sushank; B. Gupta, Brij (Bentham Science, 2015)
Radio-over-free-space-optics (Ro-FSO) is a promising technique to distribute radio frequency (RF) signals over the atmosphere using optical carriers. In this work, we designed a 60Gbps-120GHz OFDM-Ro-FSO transmission system in conjunction with mode division multiplexing. Three independent 40 GHz radio signal are optically modulated at 20 Gbps and transported over a secure free-space link of 50 km by mode division multiplexing of three Hermite-Guassian modes HG 00, HG 01 and HG 02.